Poster Presentations 2017
DOI: 10.1136/annrheumdis-2017-eular.2933
|View full text |Cite
|
Sign up to set email alerts
|

SAT0172 Economic outcomes, treatment patterns, and adverse events and reactions for patients prescribed infliximab or ct-p13 in the turkish population

Abstract: BackgroundCT-P13, a biosimilar drug product to infliximab, was approved and marketed in July 2014 in Turkey. There is little information on the costs, treatment discontinuation and adverse events and reactions between patients who switched from infliximab to CT-P13 and patients who continued infliximab.ObjectivesThe study objective was to evaluate health care costs, treatment discontinuation, and adverse events and reactions between patients who switched from infliximab to CT-P13 and patients who continued inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 0 publications
1
29
0
Order By: Relevance
“…In a large, controlled review of a Turkish healthcare administrative database, safety was compared in patients that switched from reference infliximab to CT‐P13 (n = 136) to those that continued to receive reference infliximab (n = 1388) . The adjusted incidence rate ratio (95% CI) for AEs between the groups was 0.67 (0.19, 2.30), indicating no statistically significant difference.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a large, controlled review of a Turkish healthcare administrative database, safety was compared in patients that switched from reference infliximab to CT‐P13 (n = 136) to those that continued to receive reference infliximab (n = 1388) . The adjusted incidence rate ratio (95% CI) for AEs between the groups was 0.67 (0.19, 2.30), indicating no statistically significant difference.…”
Section: Resultsmentioning
confidence: 99%
“…While the results of most of the uncontrolled, observational studies suggested that switching between reference and biosimilar infliximab products is safe and efficacious, the lack of a control arm, where patients maintain treatment with reference infliximab, makes it difficult to appropriately interpret the results. The largest controlled study found was an observational study of 1524 patients, which showed the rate of discontinuation was significantly higher in patients that switched from reference infliximab to CT‐P13 compared to those maintained on reference infliximab . However, these results should also be interpreted with caution as it was not a randomised study and the reasons for switching patients were not defined.…”
Section: Discussionmentioning
confidence: 99%
“…However, 26 (35%) studies did report a switch-back from biosimilar to originator therapy among patients who had reported worsened outcomes or who had requested to switch back to the originator therapy for other reasons [ 15 , 17 , 41 – 43 , 46 , 48 , 51 , 52 , 57 , 58 , 63 , 71 , 75 , 77 , 83 , 86 , 90 – 92 , 95 , 100 , 103 , 104 , 113 , 115 ]. Furthermore, most studies did not report whether they were powered to detect differences in efficacy or safety after the switch, although several multiple cohort studies did provide some statistical comparisons, albeit with divergent results [ 14 , 44 , 45 , 51 , 73 , 88 , 95 , 99 , 100 , 115 ]. Twenty-five (34%) studies reported immunogenicity data, and three (4%) studies reported individual patient-level immunogenicity outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Discontinuation rates were similarly variable across studies regardless of the patient population (gastroenterology, 0–50%; rheumatology, 3–87%). Only 8 (11%) studies (5 in rheumatologic conditions, 2 in IBDs, and 1 in multiple indications) compared overall raw discontinuation rates between the switch group and the historical/parallel originator continuer group, with divergent results [ 14 , 15 , 51 , 71 , 88 , 95 , 100 , 115 ]. In three studies, discontinuation rates were slightly numerically lower for continuers versus switchers (8% vs. 10% [ 51 ], 14% vs. 16% [ 14 ], and 26% vs. 29% [ 100 ], respectively), whereas in one study discontinuation rates were slightly numerically higher for continuers versus switchers (14% vs. 8% [ 88 ]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation